Impact of Initial and Boundary Conditions on Coupled Model Simulations for Bay of Bengal. Issue 2 (4th March 2022) - Patel, Shailee; Vithalpura, Manisha; Mallick, Subrat Kumar; Ratheesh, Smitha
Abstract: This study investigates the response of a high resolution coupled physical-ecosystem model simulations to initial and boundary conditions (IBCs) from various sources. For this purpose, we used physical parameters from the data sets World Ocean Atlas (WOA09), CSIRO Atlas of Regional Seas (CARS09) and North Indian Ocean Atlas (NIOA). Evaluating model simulated fields with standard validation data suggests that all three experiments could resolve most of the known surface and subsurface features of the Bay of Bengal (BoB) but with considerable differences in salinity and chlorophyll-a (Chl-a) and negligible differences in temperature among model simulations with various IBCs. The modeled Chl-a is well simulated with WOA09 as compared to NIOA and CARS09 data for climatological model simulations, with a correlation of 0.52 for the BoB. Moreover, the vertical distribution of Chl-a is found to be a function of nutrient supply to the base of the euphotic layer and mixed layer. These results significantly highlight the implicit and explicit use of IBCs for better representation of Chl-a concentration in the BoB from a high-resolution coupled model.